Blessing the couple with betel leaves - Mumbai Archive Project Team (Jio Institute, 2024)
During the haldi (turmeric) ceremony, elders bless the bride and groom with betel leaves, which are considered auspicious and often used in religious ceremonies. Betel leaves symbolize prosperity, good luck, and divine blessings.